Converging in Catholicity - PIERCE, ANDREW; DURNIN, HUGH MARY (Universal Academy Press, 2009)
The ecumenical problem and the starting point of ecumenical endeavour is that the inherent unity of the church of God has been distorted and obscured by the ecclesiastical divisions that have developed due to cultural historical and theological factors. The task of the ecumenical movement is to make visible this inherent unity, to peel away the accreations that have appended themselves to the church of God over the millennia.
PUBLISHED
Keywords: rediscovering catholicity; fullness integrity